Penerapan Akad Murabahah dalam Produk Pembiayaan Kredit Pemilikan Rumah (KPR) pada Bank Sumut Kantor Cabang Pembantu Syariah Marelan Raya - Okky Budi Nurlita; Ahmad Perdana Indra (Universitas 45 Surabaya, 2024)
This research examines the application of murabahah contracts to mortgage financing products at Bank Sumut Syariah. This research aims to understand the process of implementing the Murabahah contract in its application to mortgage financing, as well as analyzing the impact on customers and what the policies of this sharia bank are. The research method is qualitative which also involves documentation analysis and interviews with the bank. The results of this research indicate that Bank Sumut Syariah has implemented the Murabahah Agreement in its financing, especially in mortgage financing. KPR financing products have received a positive response which can help customers. Customers get benefits and benefits in product clarity. And banks can face operational and management risks that need to be addressed. The implications of this research are the basis for Sharia Banks in improving products and services, and strengthening the concept of Islamic finance in banking.